The profile of patients followed at the Neuroimmunology Clinic at UNIFESP: 20 years analysis - Denis Bernardi Bichuetti; Alessandra Billi Falcão; Fernanda de Castro Boulos; Marilia Mamprim de Morais; Claudia Beatriz de Campos Lotti; Manuela de Oliveira Fragomeni; Maria Fernanda Campos; Nilton Amorim de Souza; Enedina Maria Lobato Oliveira (Arquivos de Neuro-Psiquiatria)
Objective To describe the clinical activities at the Neuroimmunology Clinic of the Universidade Federal de São Paulo (UNIFESP) from 1994 to 2013. Method The final diagnosis of all patients that attended the center was reviewed and established upon specific guidelines for each disease. The number of total appointments and extra clinical activities (reports and prescriptions) were also analyzed, as are part of routine activities. Results 1,599 patients attended the Clinic from 1994 to 2013: 816 with multiple sclerosis (MS), 172 with clinical isolated syndromes, 178 with neuromyelitis optica (NMO), 216 with other demyelinating disease, 20 with metabolic disorder, 42 with a vascular disease and 155 with other or undetermined diagnosis. A mean 219 outpatient visits and 65 extra clinical activities were performed monthly. Conclusion We identified that 15% of patients seen have NMO. As patients with NMO have a more severe disease than MS, this data may be important for planning local health care policies.